Negative-electrode-free sodium metal battery cell as well as primary product and preparation method thereof
By adding polymer monomers and thermal decomposition initiators to the electrolyte solution without anode sodium batteries, a polymer frame layer is formed, which solves the battery volume changes and sodium dendrite problems, and improves the service life and stability of the battery.
Patent Information
- Application Number
- CN202510283711.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-11
AI Technical Summary
The volume of the negative-node sodium battery changes significantly during the battery cycle, and the gas production and sodium dendrites are severe, resulting in difficulty in selecting current collectors and affecting the stability of the module battery.
10 to 30 wt% of polymer monomer and 0.1 to 1 wt% of thermal decomposition initiator are added to the electrolyte solution, and a sodium metal coating is formed by charging with a small current, and then the initiator initiates a polymerization reaction at the polymerization temperature to form a polymer frame layer.
Through the formation of the polymer frame layer, the volume change of the battery during charging and discharging is buffered, the service life of the battery is improved, and the deposition and dissolution of sodium metal is stabilized.
Smart Images

Figure CN119812442A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery preparation, and in particular to a negative electrode-free sodium metal battery cell and a primary product and a preparation method thereof. Background Art
[0002] The negative electrode-free sodium battery is a battery that uses layered oxides (such as nickel-iron-manganese oxide and copper-iron-manganese oxide) materials, Prussian blue analogs (such as iron-based Prussian white, etc.), polyanions (such as sodium iron sulfate, sodium iron phosphate, etc.) as the positive electrode, and aluminum foil current collector as the negative electrode. It mainly uses ethers as solvents and adds Na + Metal salts (such as sodium fluoride salts, sodium borate salts and sodium perchlorate salts, etc.) electrolytes and various additives (such as film-forming, flame retardant and overcharge protection, etc.) form an electrolyte. Although negative electrode-free sodium batteries have the advantages of good low-temperature performance, low cost and high energy density, their battery volume changes significantly (significant expansion and contraction), gas production and sodium dendrites are serious. In addition, due to the two major problems of negative electrode-free sodium batteries (significant changes in battery volume, significant expansion and contraction, and growth of sodium dendrites during battery cycling), it is also quite difficult to select a suitable current collector. Therefore, the module battery of the negative electrode-free sodium battery is more significantly affected by the change in battery volume.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a negative electrode-free sodium metal battery cell and a preliminary product and a preparation method thereof, aiming to improve at least one problem mentioned in the background technology.
[0005] The present invention is achieved in that: In a first aspect, an embodiment of the present invention provides a primary product of a negative electrode-free sodium metal battery cell, including a positive electrode, a separator, a negative electrode current collector, and an electrolyte, wherein the electrolyte includes a sodium salt and an additive; The additives include polymer monomers with a concentration of 10-30wt% and thermal decomposition initiators with a concentration of 0.1-1wt% in the electrolyte; the thermal decomposition initiators can initiate polymerization of the polymer monomers at a polymerization temperature.
[0006] In an optional embodiment, the invention further includes at least one of the following features (1) to (5): (1) The polymer monomer is at least one selected from acrylonitrile, acrylate, methyl methacrylate, vinyl acetate, vinyl alcohol and styrene; (2) the thermal decomposition initiator is at least one selected from the group consisting of dibenzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dodecanoyl peroxide and dicyclohexyl peroxydicarbonate; (3) Sodium salt is at least one selected from the group consisting of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium tetrafluoroborate, sodium difluorooxalatoborate and sodium perchlorate; (4) The concentration of sodium salt is 0.8~1.2M.
[0007] (5) The solvent of the electrolyte is selected from at least one of ethylene glycol dimethyl ether and diethylene glycol dimethyl ether; (6) The active material of the positive electrode is a polyanion material, a layered oxide or a Prussian blue analogue.
[0008] In an optional embodiment, the negative electrode current collector includes a metal foil body and a conductive coating coated on the surface of the metal foil body, and the component forming the conductive coating includes carbon.
[0009] In an optional embodiment, the components forming the conductive coating further include metal powder, carbon accounts for 85-95% of the mass of the conductive coating, and the metal powder accounts for 5-15% of the mass of the conductive coating.
[0010] In an optional embodiment, the metal powder is at least one of copper powder, copper-iron alloy powder, copper-zinc alloy powder, copper-tin alloy powder and copper-nickel alloy powder.
[0011] In an optional embodiment, the metal foil body is aluminum foil; In an optional embodiment, the separator includes a base film and a modified coating applied to at least one side of the base film, the modified coating includes a solid electrolyte and a binder in a mass ratio of 9 to 19:1, and the modified coating is bonded to the negative electrode current collector.
[0012] In an optional embodiment, the invention further comprises at least one of the following features (1) and (2): (1) The solid electrolyte is selected from at least one of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte; (2) The adhesive is selected from at least one of PVDF, PMMA, CMC and SBR.
[0013] In a second aspect, an embodiment of the present invention further provides a method for preparing a negative electrode-free sodium metal battery cell, comprising: Charging the initial product of the negative electrode-free sodium metal battery cell provided in any embodiment of the present invention to a fully charged state at 0.01 to 0.1C, wherein the sodium metal is deposited on the negative electrode current collector to form a sodium metal deposition layer, thereby obtaining an intermediate battery; The intermediate battery is placed in an environment of 50 to 80°C to allow the polymer monomers in the electrolyte to polymerize and form a polymer framework layer on the metal deposition layer to obtain a finished negative electrode-free sodium metal battery cell.
[0014] In a third aspect, an embodiment of the present invention further provides an example of a negative electrode-free sodium metal battery cell, which is prepared using the preparation method provided by the present invention.
[0015] The present invention has the following beneficial effects: The preliminary product of the negative electrode-free sodium metal battery provided by the present invention can be realized because the electrolyte contains polymer monomers and thermal decomposition initiators: first, the preliminary product of the battery is charged to full power at a small current, so that a layer of metal sodium coating is deposited on the surface of the negative electrode current collector, and then the battery is placed in a polymerization temperature environment, so that the initiator triggers the polymerization reaction of the polymer monomer, and a relatively hard polymer framework layer is formed on the metal sodium coating to obtain a finished battery; in the subsequent charging and discharging process of the battery, sodium ions can pass through the polymer framework layer, and the space between the polymer framework layer and the current collector is used to deposit sodium metal during charging, and also exists during discharging, which can be used to resist the volume change of the current collector during charging and discharging, so that the volume of the battery remains basically unchanged during charging and discharging. Therefore, the preliminary product of the negative electrode-free sodium metal battery provided by the present invention can obtain a finished product of a negative electrode-free sodium metal battery with a relatively stable volume during charging and discharging after post-processing, and the battery has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 This is a SEM image of the negative electrode current collector surface of the battery of Comparative Example 1. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0019] The following is a detailed description of the negative electrode-free sodium metal battery cell and its initial product and preparation method provided in the embodiments of the present invention.
[0020] The embodiment of the present invention provides a primary product of a negative electrode-free sodium metal battery cell, which includes a positive electrode, a separator, a negative electrode current collector and an electrolyte, wherein the electrolyte includes a sodium salt and an additive; The additives include polymer monomers with a concentration of 10-30 wt% and thermal decomposition initiators with a concentration of 0.1-1 wt% in the electrolyte; the thermal decomposition initiators can initiate polymerization of the polymer monomers at a polymerization temperature.
[0021] The preliminary product of the negative electrode-free sodium metal battery provided by the present invention can be realized because the electrolyte contains polymer monomers and thermal decomposition initiators: first, the preliminary product of the battery is charged to full power at a small current, so that a layer of metal sodium coating is deposited on the surface of the negative electrode current collector, and then the battery is placed in a polymerization temperature environment, so that the initiator triggers the polymerization reaction of the polymer monomer, and a relatively hard polymer framework layer is formed on the metal sodium coating to obtain a finished battery; in the subsequent charging and discharging process of the battery, sodium ions can pass through the polymer framework layer, and the space between the polymer framework layer and the current collector is used to deposit sodium metal during charging, and also exists during discharging, which can be used to resist the volume change of the current collector during charging and discharging, so that the volume of the battery remains basically unchanged during charging and discharging. Therefore, the preliminary product of the negative electrode-free sodium metal battery provided by the present invention can obtain a negative electrode-free sodium metal battery finished product with a relatively stable volume after post-processing.
[0022] It should be noted that the amount of polymer monomer added should be within the range specified in the present invention. If too little is added, the improvement in battery cell performance will not be obvious. If too much is added, the thickness of the generated polymer framework layer will be too high, which will not only cause the battery thickness to exceed the standard, but also lead to insufficient deposition space for sodium metal.
[0023] Optionally, the polymer monomer is selected from at least one of acrylonitrile, acrylate, methyl methacrylate, vinyl acetate, vinyl alcohol and styrene; Optionally, the thermal decomposition initiator is at least one selected from dibenzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dodecanoyl peroxide and dicyclohexyl peroxydicarbonate.
[0024] When different polymer monomers are selected, an initiator for achieving polymerization thereof is selected accordingly, and an appropriate temperature for achieving the polymerization reaction is determined.
[0025] Optionally, the sodium salt is selected from at least one of sodium hexafluorophosphate, sodium bis(trifluoromethylsulfonyl)imide, sodium tetrafluoroborate, sodium difluorooxalatoborate and sodium perchlorate. It should be noted that other sodium salts disclosed in the prior art that can be used in sodium ion batteries can be applied to the present application.
[0026] Optionally, the concentration of the sodium salt is 0.8-1.2 M (e.g., 0.8 M, 1 M, or 1.2 M). This concentration range is a preferred concentration range for achieving sodium ion battery performance. It should be noted that the concentration of the sodium salt is not limited to the above range, and the suitable sodium salt concentration in the currently disclosed sodium ion battery can be applied to this application.
[0027] Optionally, the solvent of the electrolyte is selected from at least one of ethylene glycol dimethyl ether and diethylene glycol dimethyl ether.
[0028] Optionally, the positive electrode is prepared by coating a positive electrode active coating on the surface of the carbon-coated aluminum foil, wherein the positive electrode active coating is formed by a positive electrode slurry. The components of the positive electrode slurry include a positive electrode active material, a binder, a conductive agent, a dispersant and a solvent.
[0029] Specifically, the positive electrode active material is a polyanion material, a layered oxide or a Prussian blue analog. The binder may be PVDF (polyvinylidene fluoride), the conductive agent may be SP (carbon black), the dispersant may be PVP (polyvinyl pyrrolidone), and the solvent may be water or NMP.
[0030] Furthermore, the positive electrode active material, the binder, the conductive agent and the dispersant are, for example, 100:7:10:3. The solid content of the positive electrode slurry is, for example, 30-40% (eg, 30%, 35% or 40%).
[0031] Optionally, the negative electrode current collector includes a metal foil body and a conductive coating coated on the surface of the metal foil body, and the component forming the conductive coating includes carbon.
[0032] Applying a conductive coating on the surface of the negative electrode current collector can promote more uniform deposition of sodium.
[0033] Optionally, to improve the conductivity of the coating, the components forming the conductive coating also include metal powder, carbon accounts for 85-95% (e.g., 85%, 90% or 95%) of the mass of the conductive coating, and the metal powder accounts for 5-15% (e.g., 5%, 10% or 15%) of the mass of the conductive coating.
[0034] Optionally, the metal powder is at least one of copper powder, copper-iron alloy powder, copper-zinc alloy powder, copper-tin alloy powder and copper-nickel alloy powder.
[0035] Optionally, the metal foil used to prepare the negative electrode current collector is aluminum foil.
[0036] Optionally, to ensure better performance of the battery, the thickness of the conductive coating is 1 to 5 μm (eg, 1 μm, 3 μm, or 5 μm).
[0037] Optionally, the separator includes a base film and a modified coating applied to at least one side of the base film, the modified coating includes a solid electrolyte and an adhesive in a mass ratio of 9 to 19:1 (eg, 9:1, 15:1 or 19:1), and the modified coating is bonded to the negative electrode current collector.
[0038] Solid electrolyte current collectors not only have good resistance to volume deformation, but also have advantages such as high mechanical strength and high ionic conductivity. A modified coating containing solid electrolyte is coated on the surface of the diaphragm, and the modified coating side is bonded to the negative electrode current collector. This is equivalent to having a polymer framework layer and a solid electrolyte layer on the negative electrode side of the battery, which can further ensure that the electrolyte content on the negative electrode side is less and can reduce the side reactions (gas production, etc.) generated during the charging and discharging process of the sodium metal battery. Due to the fast ion conductivity of sodium ions, the solid electrolyte in the modified coating can also ensure that sodium metal can be deposited and dissolved in the polymer framework.
[0039] Optionally, the solid electrolyte is selected from polymer solid electrolytes (specifically, polyethylene oxide and polyacrylonitrile, etc.), oxide solid electrolytes (specifically, sodium lanthanum zirconium oxide, sodium aluminum titanium phosphorus and sodium aluminum oxide, etc.), sulfide solid electrolytes (specifically, Na3PS4, Na4P2S7, Na 11 Sn2PS 12 ) at least one of the following.
[0040] Optionally, the adhesive is selected from at least one of PVDF, PMMA, CMC and SBR.
[0041] Optionally, the base film is, for example, a PP (polypropylene) film.
[0042] Optionally, the modified coating has a thickness of 2-4 μm (eg, 2 μm, 3 μm, or 4 μm).
[0043] Optionally, the initial product of the negative electrode-free sodium metal battery cell provided in an embodiment of the present invention is a battery cell made by a lamination or winding process.
[0044] A method for preparing a negative electrode-free sodium metal battery cell provided by an embodiment of the present invention comprises: The initial product of the negative electrode-free sodium metal battery cell provided by the embodiment of the present invention is charged to a fully charged state at 0.01-0.1C (e.g., 0.01C, 0.05C or 1C), and the sodium metal is deposited on the negative electrode current collector to form a sodium metal deposition layer, thereby obtaining an intermediate product battery; The intermediate battery is placed in an environment of 50-80°C to allow the polymer monomers in the electrolyte to polymerize and form a polymer framework layer on the metal deposition layer to obtain a finished negative electrode-free sodium metal battery cell.
[0045] The negative electrode-free sodium metal battery cell prepared by the preparation method provided by the present invention is discharged at a normal rate. In the empty battery cell, the sodium metal basically disappears on the collector side, leaving only the negative electrode frame composed of a polymer. In subsequent cycles, the sodium metal can still be stably deposited and dissolved in the polymer frame. The polymer frame plays a key role in reducing battery deformation.
[0046] Optionally, the storage time in an environment of 50-80° C. (eg, 50° C., 60° C., 70° C., or 80° C.) is 8-20 h (eg, 8 h, 10 h, 12 h, 15 h, or 20 h).
[0047] The negative electrode-free sodium metal battery cell provided in an embodiment of the present invention is prepared by the preparation method provided in an embodiment of the present invention.
[0048] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0049] Example 1 Provide a positive electrode sheet: the positive electrode sheet includes a carbon-coated aluminum foil and a positive electrode active coating coated on the surface thereof, and the density of the positive electrode active coating is 20g / cm 2 , the coating composition includes a polyanionic compound (sodium ferric pyrophosphate), PVDF, SP, and PVP in a mass ratio of 100:7:10:3; Providing a negative electrode current collector: the current collector comprises an aluminum foil and a conductive coating coated on one side of the aluminum foil, wherein the conductive coating comprises 90% carbon and 10% copper powder, and the thickness of the modified coating is 2 μm; Providing a diaphragm: the diaphragm comprises a PP base film and a modified coating coated on one side thereof, wherein the modified coating comprises a polymer solid electrolyte (polyethylene oxide) and an adhesive (PVDF) in a mass ratio of 19:1, and the thickness of the modified coating is 4 μm; Providing an electrolyte: the electrolyte contains a solvent (diethylene glycol dimethyl ether), a sodium salt (NaPF6, concentration 1M), a polymer monomer (acrylonitrile, concentration 20wt%) and a thermal decomposition initiator (dibenzoyl peroxide, concentration 0.5wt%); The positive electrode sheet, negative electrode current collector, separator and electrolyte are assembled into a negative electrode-free battery, wherein the modified coating surface of the separator and the conductive coating surface of the negative electrode current collector are bonded together to form a primary laminated battery cell.
[0050] The stacked battery cell was charged to full charge at 0.1C, and then placed in a constant temperature environment of 50°C for 12 hours to obtain a finished negative electrode-free sodium metal battery cell.
[0051] Example 2 Provide a positive electrode sheet: the positive electrode sheet includes a carbon-coated aluminum foil and a positive electrode active coating coated on the surface thereof, and the density of the positive electrode active coating is 20g / cm 2 , the coating composition includes a polyanionic compound (sodium ferric pyrophosphate), PVDF, SP, and PVP in a mass ratio of 100:7:10:3; Providing a negative electrode current collector: the current collector comprises an aluminum foil and a conductive coating coated on one side of the aluminum foil, wherein the conductive coating comprises 95% carbon and 5% copper powder, and the thickness of the modified coating is 3 μm; Provide a diaphragm: The diaphragm includes a PP base film and a modified coating coated on one side thereof, wherein the modified coating includes a sulfide solid electrolyte (Na3PS4) and an adhesive (PVDF) in a mass ratio of 9:1, and the thickness of the modified coating is 2 μm.
[0052] Providing an electrolyte: The electrolyte contains a solvent (diethylene glycol dimethyl ether), a sodium salt (NaPF6, concentration 1M), a polymer monomer (acrylate, concentration 30wt%) and a thermal decomposition initiator (azobisisobutyronitrile, concentration 1wt%).
[0053] The positive electrode sheet, negative electrode current collector, separator and electrolyte are assembled into a negative electrode-free battery, wherein the modified coating surface of the separator and the conductive coating surface of the negative electrode current collector are bonded together to form a primary laminated battery cell.
[0054] The stacked battery cell was charged to full charge at 0.1C, and then placed in a constant temperature environment of 80°C for 12 hours to obtain a finished negative electrode-free sodium metal battery cell.
[0055] Example 3 Provide a positive electrode sheet: the positive electrode sheet includes a carbon-coated aluminum foil and a positive electrode active coating coated on the surface thereof, and the density of the positive electrode active coating is 20g / cm 2 , the coating composition includes a polyanionic compound (sodium ferric pyrophosphate), PVDF, SP and PVP in a mass ratio of 100:7:10:3; Providing a negative electrode current collector: the current collector comprises an aluminum foil and a conductive coating coated on one side of the aluminum foil, the conductive coating comprising 85% carbon and 15% copper powder, the thickness of the modified coating is 1μm; Provide a diaphragm: The diaphragm includes a PP base film and a modified coating coated on one side thereof, wherein the modified coating includes a layered oxide solid electrolyte (sodium aluminum titanium phosphorus) and an adhesive (PVDF) in a mass ratio of 15:1, and the thickness of the modified coating is 3 μm.
[0056] Providing an electrolyte: The electrolyte contains a solvent (diethylene glycol dimethyl ether), a sodium salt (NaPF6, concentration 1M), a polymer monomer (vinyl alcohol, concentration 10wt%) and a thermal decomposition initiator (azobisisoheptanenitrile, concentration 0.1wt%).
[0057] The positive electrode sheet, negative electrode current collector, separator and electrolyte are assembled into a negative electrode-free battery, wherein the modified coating surface of the separator and the conductive coating surface of the negative electrode current collector are bonded together to form a primary laminated battery cell.
[0058] The stacked battery cell was charged to full charge at 0.1C, and then placed in a constant temperature environment of 65°C for 12 hours to obtain a finished negative electrode-free sodium metal battery cell.
[0059] Example 4 This embodiment is basically the same as Embodiment 1, except that no modified coating is provided on the surface of the diaphragm.
[0060] Example 5 This embodiment is basically the same as Embodiment 4, except that no conductive coating is provided on the surface of the negative electrode current collector.
[0061] Comparative Example 1 This comparative example is basically the same as Example 5, except that the electrolyte does not include polymer monomers and initiators.
[0062] Comparative Example 2 This comparative example is basically the same as Example 5, except that the concentration of the polymer monomer in the electrolyte is 50 wt %.
[0063] Example 1 The battery cell prepared in Example 1 was disassembled and a SEM image of the negative electrode current collector was taken. Figure 1 As shown, from Figure 1 It can be seen that the battery of the embodiment forms a polymer framework on the surface of the negative electrode current collector.
[0064] Experimental Example 2 The electrochemical performance of the prepared negative electrode-free sodium metal battery was tested, and the exhaust volume was measured. The exhaust volume test method was the water displacement method, which is: a water cylinder is placed on an electronic balance, and the soft-pack battery is placed in the water, which is just immersed in the water. Principle: Archimedes, F 浮 =G 排 =ρ 水 V 排 , ρ 水 g=10. V 排 =1 / 10 F 浮 =The weight shown on the electronic scale (g).
[0065] Table 1 Test results of various embodiments and comparative examples
[0066] It can be seen from Table 1 that the batteries prepared in various embodiments of the present invention have better capacity retention than that of Comparative Example 1, indicating that the preliminary product of the negative electrode-free sodium metal battery cell provided by the present invention, due to the addition of polymer monomers and thermal decomposition initiators in the electrolyte, can form a polymer framework layer on the surface of the negative electrode current collector after subsequent heat treatment to buffer the volume change of the battery and improve the service life of the battery.
[0067] Comparing Example 4 with Example 1, the capacity retention rate of Example 1 is better, indicating that coating the modified coating containing the solid electrolyte on the surface of the diaphragm can make the ion conductivity of the diaphragm better, thereby improving the capacity retention rate of the battery cell; Comparing Example 5 with Example 4, the capacity retention rate of Example 4 is better, indicating that providing a conductive coating on the negative electrode current collector can promote uniform deposition of sodium metal, improve electronic conductivity, and thus improve the capacity retention rate of the battery cell; Comparing Comparative Example 2 with Example 5, the cyclability of Comparative Example 2 is significantly worse, even worse than Comparative Example 1, indicating that excessive addition of polymer monomers in the electrolyte will result in too few electrolyte ions, affecting normal ion migration.
[0068] In summary, the negative electrode-free sodium gold core and its initial product and preparation method provided by the embodiment of the present invention have the following characteristics: Due to the appropriate addition of polymer monomers and thermal decomposition initiators in the electrolyte, the battery cell can form a polymer framework layer on the surface of the sodium metal deposition layer at a suitable temperature. The formation of the polymer framework layer can buffer the volume change of the battery cell during the charging and discharging process and improve the service life of the battery cell.
[0069] In a preferred embodiment, the provision of a modified coating containing a solid electrolyte on the surface of the diaphragm can further reduce the amount of electrolyte on the negative electrode side and reduce the side reactions (gas production, etc.) generated on the negative electrode side during the charge and discharge process of the sodium metal battery; in a preferred embodiment, the provision of a conductive coating on the surface of the negative electrode current collector can further promote uniform deposition of sodium.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A primary product of a negative electrode-free sodium metal battery cell, characterized in that: The invention comprises a positive electrode, a separator, a negative electrode current collector and an electrolyte, wherein the electrolyte comprises a sodium salt and an additive; The additives include a polymer monomer with a concentration of 10-30wt% and a thermal decomposition initiator with a concentration of 0.1-1wt% in the electrolyte; the thermal decomposition initiator can initiate a polymerization reaction of the polymer monomer at a polymerization temperature.
2. The primary product of the negative electrode-free sodium metal battery cell according to claim 1, characterized in that: It also includes at least one of the following features (1) to (5): (1) The polymer monomer is at least one selected from acrylonitrile, acrylate, methyl methacrylate, vinyl acetate, vinyl alcohol and styrene; (2) The thermal decomposition initiator is at least one selected from dibenzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dodecanoyl peroxide and dicyclohexyl peroxydicarbonate; (3) The sodium salt is at least one selected from the group consisting of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium tetrafluoroborate, sodium difluorooxalatoborate and sodium perchlorate; (4) The concentration of the sodium salt is 0.8~1.2M; (5) The solvent of the electrolyte is selected from at least one of ethylene glycol dimethyl ether and diethylene glycol dimethyl ether; (6) The active material of the positive electrode is a polyanion material, a layered oxide or a Prussian blue analogue.
3. The primary product of the negative electrode-free sodium metal battery cell according to claim 1, characterized in that: The negative electrode current collector comprises a metal foil body and a conductive coating coated on the surface of the metal foil body, and the component forming the conductive coating comprises carbon.
4. The primary product of the negative electrode-free sodium metal battery cell according to claim 3, characterized in that: The components forming the conductive coating further include metal powder, the carbon accounts for 85-95% of the mass of the conductive coating, and the metal powder accounts for 5-15% of the mass of the conductive coating.
5. The primary product of the negative electrode-free sodium metal battery cell according to claim 4, characterized in that: The metal powder is at least one of copper powder, copper-iron alloy powder, copper-zinc alloy powder, copper-tin alloy powder and copper-nickel alloy powder.
6. The primary product of the negative electrode-free sodium metal battery cell according to claim 3, characterized in that: The metal foil body is aluminum foil.
7. The primary product of the negative electrode-free sodium metal battery cell according to claim 1, characterized in that: The separator includes a base film and a modified coating coated on at least one side of the base film, the modified coating includes a solid electrolyte and an adhesive in a mass ratio of 9 to 19:1, and the modified coating is bonded to the negative electrode current collector.
8. The primary product of the negative electrode-free sodium metal battery cell according to claim 7, characterized in that: Also includes at least one of the following features (1) and (2): (1) The solid electrolyte is selected from at least one of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte; (2) The adhesive is selected from at least one of PVDF, PMMA, CMC and SBR.
9. A method for preparing a negative electrode-free sodium metal battery cell, characterized in that: include: The initial product of the negative electrode-free sodium metal battery cell according to any one of claims 1 to 8 is charged to a fully charged state at 0.01 to 0.1 C, and the sodium metal is deposited on the negative electrode current collector to form a sodium metal deposition layer, thereby obtaining an intermediate battery; The intermediate battery is placed in an environment of 50 to 80° C. to polymerize the polymer monomers in the electrolyte, forming a polymer framework layer on the metal deposition layer, and obtaining the finished product of the negative electrode-free sodium metal battery cell.
10. A negative electrode-free sodium metal battery cell, characterized in that: The method according to claim 9 is used to prepare the product.
Citation Information
Cited By
Current collector for negative electrode, sodium ion battery, preparation method and application
CN121460592A